Program Pembuatan Pupuk Kompos Padat Limbah Kotoran Sapi Dan Ampas Kopi Dengan Metode Fermentasi Menggunakan EM4 Dan Molases Di Desa Mekar Indah - Saputra, Whin Themas Mico; Alfayet, Dodi; Chatami, M.Rizki; Nosra, Rezeki; Muntaha, Ranto; Munthe, Farhan; Agustian, Teguh; Ichwan, Ichwan; Ramadhan, Syahrin; Saleh, Ilham; Fitri, Daini; Ayu, Nadia; Rizki, Arami; Lismayanti, Lismayanti; Pinteniate, Pinteniate (Universitas Gajah Putih, Indonesia, 2024)
The covid-19 pandemic in early 2020 has caused a decline in the value of banking companies in Indonesia. The limited space for people to move due to government policies has an impact on reducing economic activity and disrupting bank performance in providing credit. This study was conducted to determine the effect of profitability and liquidity on firm value with dividend policy as a moderating variable. The population in this study were 47 banking companies listed on the Indonesia Stock Exchange with an observation time of 4 years. The sampling method used in this study was purposive sampling, and the number of samples obtained was 12 banking companies. The data analysis method used is Moderated Regression Analysis (MRA) using SMART PLS 4. Based on the research results, profitability has a positive and significant effect on firm value while liquidity has a negative and significant effect on firm value. Meanwhile, dividend policy cannot moderate the effect of profitability and liquidity on the value of banking companies listed on the Indonesia Stock Exchange for the 2019-2022 period.